Pengaruh Inovasi dan Brand Image terhadap Repurchase Intention Dengan Kepuasan Pelanggan sebagai Variabel Intervening - paramitha, Pasuhuk anggie (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
The purpose of this study is to determine the effect of Innovation and Brand Image on Repurchase Intention with Customer Satisfaction as intervening variable, especially on Go-Jek’s customers in Manado Cit. Data are collected through questionnaire, interviews, and library research. The numbers of respondents in this study are 400 customers who are using Go-Jek’s services in Manado City. The results show that: 1) innovation has positive and significant effect on customer satisfaction; 2) brand image has positive and significant effect on customer satisfaction; 3) innovation and brand image simultaneously have positive and significant effect on customer satisfaction; 4) innovation has positive and significant effect on repurchase intention; 5) brand image has positive and significant effect on repurchase intention; 6) customer satisfaction has positive and significant effect on repurchase intention; 7) innovation, brand image, and customer satisfaction simultaneously have positive and significant effect on repurchase intentionKeywords: Innovation, Brand Image, Customer Satisfaction, and Repurchase Intention